2019
DOI: 10.2147/ceg.s206194
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of <em>IFNL3</em> rs12979860 polymorphism with HCV-related hepatocellular carcinoma susceptibility in a Chinese population</p>

Abstract: BackgroundThe association between interferon lambda-3 (IFNL3,also known as interleukin 28B, IL28B) rs12979860 polymorphism and the development of hepatocellular carcinoma (HCC) has been investigated in recent studies with inconclusive and inconsistent results. IFNL3 rs12979860 polymorphism has been shown a marked differential distribution with regional and ethnic variation. Whether this single nucleotide polymorphism influences susceptibility to hepatitis C virus (HCV)-related HCC remains elusive.MethodsIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…As compared to the C allele, where the prevalence in CLD versus HCC groups was 30% and 50%, respectively, but the differences between the groups were not significant[ 42 ]. Our results were similar to a recent study conducted on the Chinese population, which found that the T allele was associated with a higher risk of HCV-related HCC[ 43 ]. A recent meta-analysis found a strong correlation between IL-28B genetic polymorphism and HCC association with HBV or HCV infection, where CC and TT genotypes of certain single nucleotide polymorphisms (SNPs) of IL-28B were protective against HCC occurrence[ 44 ].…”
Section: Discovering New Biomarkers: Molecular Pathways Discovery and Determining Of The Genetic-epigenetic-phenotypic Linkage Through CLsupporting
confidence: 92%
“…As compared to the C allele, where the prevalence in CLD versus HCC groups was 30% and 50%, respectively, but the differences between the groups were not significant[ 42 ]. Our results were similar to a recent study conducted on the Chinese population, which found that the T allele was associated with a higher risk of HCV-related HCC[ 43 ]. A recent meta-analysis found a strong correlation between IL-28B genetic polymorphism and HCC association with HBV or HCV infection, where CC and TT genotypes of certain single nucleotide polymorphisms (SNPs) of IL-28B were protective against HCC occurrence[ 44 ].…”
Section: Discovering New Biomarkers: Molecular Pathways Discovery and Determining Of The Genetic-epigenetic-phenotypic Linkage Through CLsupporting
confidence: 92%
“…In one Chinese MAFLD cohort, researchers found that the neurocan (known as NCAN ) rs2228603 T variant associated with a higher level of high-density lipoprotein, 21 while it was positively related to liver steatosis in the USA population. 22 Similarly, toll-like receptor 3 (known as TLR3 ) rs3775290 23 , 24 and interferon lambda-3 (known as IFNL3 ) rs12979860 25 , 26 variants in Chinese hepatocellular carcinoma populations showed opposite effects to those in non-Asian populations. Inconsistent results have also been observed in other Asian populations, such as among Japanese.…”
Section: Discussionmentioning
confidence: 99%
“… 28 A study on IL-28 genetic polymorphisms revealed the association of the T allele with higher risk of HCC development. 29 Another study revealed that two genotypes of certain single nucleotide polymorphisms (SNPs) of IL-28 were associated with lower risk of HCC development. 30 Thus, the role of IL28 in diagnosing and prognosticating HCC appears unclear, if not contradictory.…”
Section: Molecular Markers For Hepatocellular Diseasesmentioning
confidence: 99%